2007
DOI: 10.1158/0008-5472.can-06-2746
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CCAAT/Enhancer Binding Protein Family DNA Binding in Mouse Epidermis Prevents and Regresses Papillomas

Abstract: The CCAAT/enhancer binding proteins (C/EBP) are a family of B-ZIP DNA binding proteins that act as transcription factors to regulate growth and differentiation of many cell types, including keratinocytes. To examine the consequences of inhibiting the C/EBP family of transcription factors in skin, we generated transgenic mice that use the tetracycline system to conditionally express A-C/EBP, a dominant negative that inhibits the DNA binding of C/EBP family members. We expressed A-C/EBP in the basal layer of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 44 publications
(63 reference statements)
1
47
0
Order By: Relevance
“…Expression of C/EBPa increases on differentiation and seems to be specific to the suprabasal layers, which suggests it might play a role in epidermal differentiation (Rishi et al 2010). Further, the overexpression of C/EBPa in the skin leads to hyperplasia of the basal layer of the epidermis whereas its down-regulation in vitro results in inhibition of differentiation (Oh et al 2007;Rishi et al 2010). These phenotypes are compatible with the role of C/EBPa in inducing expression of methylated genes involved in skin differentiation.…”
Section: The Role Of Dna Methylation In Skin Differentiationsupporting
confidence: 54%
See 1 more Smart Citation
“…Expression of C/EBPa increases on differentiation and seems to be specific to the suprabasal layers, which suggests it might play a role in epidermal differentiation (Rishi et al 2010). Further, the overexpression of C/EBPa in the skin leads to hyperplasia of the basal layer of the epidermis whereas its down-regulation in vitro results in inhibition of differentiation (Oh et al 2007;Rishi et al 2010). These phenotypes are compatible with the role of C/EBPa in inducing expression of methylated genes involved in skin differentiation.…”
Section: The Role Of Dna Methylation In Skin Differentiationsupporting
confidence: 54%
“…In mammalian genomes, up to 80% of the CpG sequences are methylated, and most of the unmethylated CpG are found in regions of high CpG content, known as CpG islands (Reik 2007), close to the promoters and first exons of actively transcribed genes. Although DNA methylation is generally associated with transcriptional repression, there are some examples in which 5mC is thought to mediate gene expression by recruitment of the mCpG-binding protein C/EBPa (CRE enhancer-binding protein alpha-isoform), which functions as a transcriptional activator (Oh et al 2007;Rishi et al 2010). …”
Section: Dna Methylationmentioning
confidence: 99%
“…C/EBPα is expressed in various highly differentiated cells and tissues, including peripheral blood mononuclear cells, and adipose, liver and lung tissues (7). Previous studies have demonstrated that C/EBPα is expressed in every layer of the epidermis; therefore, C/EBPα may regulate the proliferation and differentiation of keratinocytes (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…1C). We chose to study C/EBPα in more detail because it is involved in the activation of differentiation in several cell types (15), including keratinocytes (16)(17)(18) and adipocytes (19)(20)(21), potentially linking C/EBPα binding to methylated promoters with activation of methylated promoters upon differentiation (see below).…”
mentioning
confidence: 99%
“…First, we cultured primary keratinocytes from transgenic mice expressing a dominant-negative protein (A-C/EBP) that inhibits the DNA binding of C/EBP family members (18). Second, we used siRNA to deplete C/EBPα and C/EBPβ (SI Appendix, Fig.…”
mentioning
confidence: 99%